Web-Application for securing message using Steganography with LSB Algorithm and Hybrid Encryption / Muhammad Khairul Amin Mohd Nai and Siti Rahayu Abdul Aziz - Mohd Nai, Muhammad Khairul Amin; Abdul Aziz, Siti Rahayu (UiTM Cawangan Melaka Kampus Jasin, 2021)
Web-Application for Securing Message using Steganography with LSB Algorithm and Hybrid Encryption is a web application that encrypt the messages user input and hide it in an image file to give an utmost security for the messages to be delivered and received. This web application was developed for any users especially for the company who wished to send a confidential message without worrying of being compromised by man-in-the-middle attack or internal attack. The output of the image file that embedded with the messages were sent to the drive or cloud so, that anyone can access it but only can be accessed by those who have the password. The application also features decryption. The benefits of using this system are that messages hidden will be unbeknown and unsusceptible to be stolen since the it was hide in an ordinary looking file which is an image. Even if managed to be decrypt the steganalysis, the hybrid features of encryption will surely hinder or slowing it greatly to be decrypted. In term of security, it can be said to be impenetrable.